2020
DOI: 10.1080/2090598x.2020.1733818
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of multiparametric magnetic resonance imaging in bladder cancer (Vesical Imaging-Reporting and Data System): A systematic review

Abstract: 2020) The effectiveness of multiparametric magnetic resonance imaging in bladder cancer (Vesical Imaging-Reporting and Data System): A systematic review, ABSTRACT Objective: To evaluate the role of the Vesical Imaging-Reporting and Data System (VI-RADS) score in the diagnostic pathway of bladder cancer. Methods: A systemic search of the contemporary literature was performed in December 2019 using the Medical Literature Analysis and Retrieval System Online (MEDLINE), the Excerpta Medica dataBASE (EMBASE), and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Several recent meta-analyses showed that with a score of 3 or 4 as the cut-off value, the VI-RADS scoring system provided good diagnostic performance for evaluating muscle invasion. 12,17,31 The agreement between the two observers in the VI-RADS scoring system was excellent both in the concordant group and discordant group with using high-resolution T2WI, DCE, and rFOV DWI, and this agreed well with previous studies. Wang indicated that the consistency between the two readers was excellent in VI-RADS, while the disagreement mainly occurred in the lesions located in the bladder neck and bilateral ureteral orifices.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Several recent meta-analyses showed that with a score of 3 or 4 as the cut-off value, the VI-RADS scoring system provided good diagnostic performance for evaluating muscle invasion. 12,17,31 The agreement between the two observers in the VI-RADS scoring system was excellent both in the concordant group and discordant group with using high-resolution T2WI, DCE, and rFOV DWI, and this agreed well with previous studies. Wang indicated that the consistency between the two readers was excellent in VI-RADS, while the disagreement mainly occurred in the lesions located in the bladder neck and bilateral ureteral orifices.…”
Section: Discussionsupporting
confidence: 87%
“…5 The aim of this scoring system was to standardize MR imaging and reporting. Many studies and meta-analyses [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have validated the diagnostic accuracy of the VI-RADS scoring system in the detection of muscle-invasiveness, underscoring the value of this system in the diagnostic workup and management of patients with BCa. However, scoring of this system is subjective and the position of the tumor may affect its accuracy.…”
mentioning
confidence: 99%
“…The results obtained in the studies indicate that the standardizing VI-RADS is an effective comprehensive scoring system, with a high satisfactory sensitivity, specificity, and diagnostic value for determining the probability of invasion of the bladder detrusor muscle invasion in bladder cancer (6,19,20).…”
Section: Diagnostic Performance Of Vi-radsmentioning
confidence: 91%
“…There is an agreement between authors of many studies that there is a need to test mpMRI in clinical practice before it could be established as a crucial part of bladder cancer management (6,20,24,25,26,27).…”
Section: Disadvantages Of Vi-radsmentioning
confidence: 99%
See 1 more Smart Citation